THE INFLUENCE OF CONSUMER INTENTION TO ADOPT MOBILE BANKING APPLICATIONS: A REVIEW OF THEORETICAL FRAMEWORKS - Zaidie Chen; Fatihah Mohd; Nur Ain Ayunni Sabri, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
In today's digital landscape, mobile banking has become a core element of the financial sector, providing both convenience and greater accessibility for customers. Nevertheless, identifying the elements that truly drive user adoption and subsequent engagement remains a significant hurdle for banking institutions. This research sets out to investigate the nuanced aspects of how users adopt technology, focusing specifically on the context of Hangzhou City Commercial Bank. By exploring the lasting impact of factors such as perceived external control and an individual's computer playfulness, this study aims to deepen understanding regarding the intentions and actual behaviors demonstrated by those who use mobile banking services. Drawing upon the foundation of the Technology Acceptance Model 3 (TAM3), the research plan integrates perceived ease of use to act as a mediating variable, helping dissect the intricate connections between outside influences and a user's intention to behave in a certain way. The study employ a quantitative research framework, utilizing a structured questionnaire intended for distribution among customers of Hangzhou City Commercial Bank, with a target sample size of five hundred participants. Key steps in the methodology encompass a thorough literature review, the process of developing the survey instruments, gathering the necessary data, and conducting statistical analysis, primarily through structural equation modeling. Ultimately, this research endeavor intends to uncover the underlying motivators impacting user uptake, thereby offering valuable, actionable insights for the bank to refine and improve its mobile banking service offerings. The anticipated results stand to contribute meaningfully to both advancements in the theory behind technology acceptance models and practical recommendations for the financial sector aiming to boost user involvement and overall satisfaction. This document presents the foundational reasons, theoretical background, planned methods, and expected contributions of the upcoming study, welcoming further discussion and critique to refine and solidify the design of this research initiative.